Sleep quality and cerebrospinal fluid oxysterols in degenerative dementias: correlations and possible biomedical implications - Luca Pradotto; Stefania Cattaldo; Lorenzo Priano; Riccardo Cremascoli; Elisa Prina; Alessandra Milesi; Stefania Mai; Paolo Piterà; Domenico Tripodi; Giuseppe Poli; Valerio Leoni; Alessandro Mauro (Redox Experimental Medicine)
Objective: The combination and tentative correlation of a selected set of polysomnographic tests with the quantitative measurement of oxysterols of pathophysiological relevance in the cerebrospinal fluid (CSF) of patients with Alzheimer’s degenerative dementia (AD), non-Alzheimer’s degenerative dementia (NAD) and nondegenerative disorders (C) were afforded in a pilot study. Methods: Sleep efficiency, percentage of sleep time spent in nonrapid eye movement (NREM) stage 3 (N3), apnea/hypopnea index and sleep time spent with oxygen saturation <90% were recorded. Oxysterols of both enzymatic and nonenzymatic origin were quantified in the CSF of the three groups of patients by isotope-dilution gas chromatography mass spectrometry. Results: A remarkable increase in all tested oxysterols of autoxidation origin and of cholesterol was detectable in the CSF of AD and NAD patients in comparison with C patients. Of the four markers of sleep quality tested, only the percentage duration of N3 showed a net progressive reduction in NAD and AD patients. A strong inverse correlation between the CSF levels of 7k-cholesterol (7KC) and 7α-hydroxycholesterol and the duration of N3% in the recruited cohorts of patients appeared evident. Conclusions: An abnormal increase in some oxysterols of autoxidation origin, particularly of 7KC, in the CSF of patients with degenerative dementia, with the highest levels reached in AD patients, appears to be a reliable candidate biomarker of reduced duration of N3 sleep. The observed accumulation of oxysterols in the CSF seems at least in part because of impaired efficiency of the glymphatic system, which indeed reaches, under normal conditions, its maximum activity in the N3 sleep phase. A contribution of altered cholesterol metabolism to sleep quality in AD patients cannot be excluded. Significance statement: Oxysterols of nonenzymatic origin are proposed as new CSF candidate markers of sleep quality in patients with dementia.